Nouvelles de nulle part - Collie, Van Christophe (Belgium, 2010)
A former garbage dumb, transformed by the government into gardens, is threatened by a construction project. An association of residents and occupants of the gardens struggle to preserve the site.
Verzio Film Festival Submission
Keywords: Documentary films